Islamic Education Management: Promoting Literacy and Social Transformation of Urban Muslims in Facing the Challenges of Globalization - Devi Fatwanti; Moch Faisal; Mukhriji Mukhriji; Encep Syarifudin; Eneng Muslihah; Siti Patimah (EDUJAVARE: International Journal of Educational Research, 2026)
This study examines the relationship between Islamic literacy and social awareness among urban Muslim communities in the context of accelerating globalization, with particular attention to Indonesia as the world’s largest Muslim-majority nation. Employing a Systematic Literature Review (SLR) guided by PRISMA protocol, the study systematically screened 312 scholarly publications retrieved from Scopus, Web of Science, Google Scholar, ERIC, DOAJ, and SINTA databases, covering the period 2018–2024. Following a rigorous three-stage selection procedure, 87 studies met the inclusion criteria and were subsequently analyzed through a narrative-thematic synthesis approach. The findings reveal that Islamic literacy is inherently multidimensional, encompassing four analytically distinct yet interrelated dimensions: textual-classical, critical-interreligious, digital-media, and social-civic. These dimensions operate synergistically through four principal mechanisms: the formation of scripture-grounded ethical character, the cultivation of critical capacity for social resilience, the reinforcement of communal identity as a driver of prosocial action, and the development of cross-cultural competence. The evidence strongly indicates that when Islamic literacy is developed in an integrative manner, it functions simultaneously as a protective and constructive force reducing individual susceptibility to disinformation and extremist recruitment, nurturing inclusive and moderate religious identity, and strengthening ethically-grounded civic participation. Mosque-based literacy programs, institutionalized digital literacy initiatives, and formal Islamic educational institutions each play vital roles in producing Muslim communities capable of robust and socially responsible engagement with contemporary challenges. The study concludes that rather than rendering Islamic literacy obsolete, the era of globalization intensifies its urgency as a foundational resource for social consciousness.